A national soul : Canadian mural painting, 1860s-1930s - McKay, Marylin Jean, 1944- (McGill-Queen's University Press, 2002)
"Bringing together a body of work that has been largely ignored by art historians, A National Soul challenges previous histories of Canadian painting. This generously illustrated book reproduces seldom-seen murals and includes a comprehensive listing of all works from the period, their original and present locations, and their state of preservation."--Jacket